Validasi Metoda Analisa Kadar Logam Pb pada Rambut Karyawan SPBU jln. Juanda Kota Padang - Dyna Putri Mayaserli; Retnowati Retnowati (Universitas Ahmad Dahlan, 2019)
Development in the health sector is the achievement of optimal public health degrees. People who are often exposed to air pollution, one of them is a gas station officer, for example lead metal (Pb). One of the objectives of this study was to determine differences in the cost (Pb) in the hair of gas station workers on Jl. Ir. Juanda is based on the length of the working period by using an experimental type of research to analyze Pb metal on gas station employees. The population and sample of the study were 3 gas station employees' hair containing 3 people. The sampling technique is based on the length of work. The results of this study found that the longer the employee's working period the higher the Pb level in the employee's hair and the percentage recovery value for the method of wet destruction using HNO3 and HCLO4 had an average recovery of 96.23% where the precision test was 4.01%. It is recommended that the next validation test use another method, namely dry destruction and review of parameters about age, place of birth date and lifestyle.